2021
DOI: 10.3390/ijms22094332
|View full text |Cite
|
Sign up to set email alerts
|

miR-155 as an Important Regulator of Multiple Sclerosis Pathogenesis. A Review

Abstract: Multiple sclerosis (MS) is a chronic, immune-mediated disease and the leading cause of disability among young adults. MicroRNAs (miRNAs) are involved in the post-transcriptional regulation of gene expression. Of them, miR-155 is a crucial regulator of inflammation and plays a role in modulating the autoimmune response in MS. miR-155 is involved in blood–brain barrier (BBB) disruption via down-regulation of key junctional proteins under inflammatory conditions. It drives demyelination processes by contributing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 122 publications
0
34
0
1
Order By: Relevance
“…miR-155 exhibited upregulated cerebral expression in MS patients or experimental models [ 171 173 ]. Lopez-Ramirez et al showed that loss of miR-155 reduced BBB extravasation of both experimental autoimmune encephalomyelitis (EAE) and in an acute systemic inflammation model induced by lipopolysaccharide [ 172 ].…”
Section: Non-coding Rnas Regulate Bbb/bscb Functions In Cns Disordersmentioning
confidence: 99%
“…miR-155 exhibited upregulated cerebral expression in MS patients or experimental models [ 171 173 ]. Lopez-Ramirez et al showed that loss of miR-155 reduced BBB extravasation of both experimental autoimmune encephalomyelitis (EAE) and in an acute systemic inflammation model induced by lipopolysaccharide [ 172 ].…”
Section: Non-coding Rnas Regulate Bbb/bscb Functions In Cns Disordersmentioning
confidence: 99%
“…On the other hand, the literature review highlighted that miR-155 is a pivotal regulator in the inflammation pathway and modulated an autoimmune response. Furthermore, a recent study had shown that inhibition of miR-155 led to the prevention of pathophysiological mechanisms involved in multiple sclerosis incidence [ 48 ]. Moreover, Forough Taheri reported that miR-34 has a potential role in Th17 cell differentiation induction, and up-regulation of miR-34 could lead to progressive multiple sclerosis status, and down-regulation of miR-34 might ameliorate multiple sclerosis condition [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing EV miRNA profiles among the spinal cord (SP), plasma, and urine at the pre-onset, onset, and peak stages of EAE disease, the authors found an overexpression of EV-derived miR-155-5p during pre-onset [ 66 ]. This miRNA, also known as inflamma-miR, is a strong regulator of inflammation, modulating the autoimmune response in MS [ 80 ]. They also examined the effect of glatimer acetate (GA), usually used in MS therapy, on miRNA expression, showing, for the first time, that under treatment, especially in urinary EV miRNAs, expression was modulated, and miR-9-5p and miR-35-3p were significantly deregulated at the EAE peak stage.…”
Section: Evs’ Cargo: Reservoir Of Potential Biomarkers For Msmentioning
confidence: 99%